Mechanism of neuroprotection by magnesium acetyltaurate on experimental glutamate-induced excitotoxicity in rat retinal ganglion cells / Associate Professor Dr Igor Nikolayevich Iezhitsa and Dr. Khairul Nizam Rozali - Rozali, Khairul Nizam; Igor, Nikolayevich Iezhitsa (Research Management Institute (RMI), 2016)
Glaucoma is characterized by damage to the optic nerve, which leads to progressive and irreversible vision loss (Casson et al. 2012). It is the second most common cause of blindness worldwide after cataract. It is estimated that 4.5 million people are suffering from glaucoma-related blindness and this number is expected to rise to 11.2 million by 2020 (Quigley and Broman 2006). Most therapies for glaucoma are directed at the reduction of the intraocular pressure (IOP). Conventional wisdom holds that excessive pressure within the eye leads to retinal ganglion cell (RGC) loss and optic nerve damage seen in this disease. However, the elevated IOP is only one of the risk factors that lead to RGC apoptosis. Several other risk factors also contribute to RGC loss in glaucoma. Studies have shown that many of these risk factors culminate into glutamate-mediated toxicity to RGCs and glutamate selectively damages RGCs in the mammalian eye (Dreyer and Lipton 1999). Glutamate is the principal excitatory neurotransmitter in the central nervous system (CNS). However, excessive activation of glutamate-gated membrane channels may lead to irreversible injury to neurons. Glutamatergic excitotoxicity, results primarily from intracellular accumulation of calcium ions and in retina it was first described by Lucas and Newhouse (1957). Because of the relatively high permeability of N-methyl-D-aspartate (NMDA)-type glutamate- gated channels to calcium ions, neurons are particularly sensitive to injury associated with excessive activity of this channel subtype (Choi 1988). RGCs are known to express NMDA-type channels, and glutamatergic excitotoxicity, mediated by NMDA channels, has been demonstrated to contribute significantly to RGC injury in both the in vitro and animal models (Levy and Lipton 1990; Sucher et al. 1991; Kitano et al. 1996; Pang et al. 1999; Luo et al. 2001). From a therapeutic standpoint, NMDA receptors are potential targets of intervention to prevent RGC death (Lipton 1993; Chidlow et al. 2007; Russo et al. 2008). Glutamate, however, mediates synaptic transmission essential for normal function of the nervous system. Hence, complete blockade of NMDA receptor activity causes unacceptable side effects (Seki and Lipton 2008)…